Athlete typology and training strategy in the 400 m hurdles - Iskra, J. (New Studies in Athletics, 2012)
Most coaches will find themselves with athletes who vary from any established ideal set of characteristics, making it necessary develop an appropriate training strategy to maximise each individual athlete's potential. For them, the most interesting analysis of training concerns groups of similar athletes - defined by body build, motor and coordinative (technical, rhythm) preparation, personality and the specifics of their sport careers - so that the relevant lessons and information can be applied in practice. In a previous study the author, who is a coach and scientist, created a typology of 400m hurdlers and found there were seven basic types of top performers in the event. The aim of this article is to systematically present the appropriate training means for the three types of 400m hurdlers seen most often in the early 21st century: "Special Endurance", "Technical" and "Rhythm" and to show how these means are incorporated into microcycles for each of the main training periods as a guide for coaches who are planning a programme. Templates of endurance, strength and rhythm training means have been prepared for each type of hurdler. In addition, sample microcycles for the "general preparation", "special preparation" and "pre-competition/competition" periods are presented.